2019
DOI: 10.1007/s11162-019-09548-w
|View full text |Cite
|
Sign up to set email alerts
|

The Correlates of Credit Loss: How Demographics, Pre-Transfer Academics, and Institutions Relate to the Loss of Credits for Vertical Transfer Students

Abstract: Despite the long-standing centrality and growing prevalence of transfer in the American postsecondary system, students, college professionals, and policymakers decry the lack of credit transferability between colleges. However, limited research has examined the factors most related to the magnitude of credit loss students experience. This study investigated how students’ pre-transfer academic characteristics, demographic characteristics, and the institutions they transferred to and from influenced the magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…However, Turk (2018) found that earning an associate's degree prior to transfer has no impact on the likelihood of completing a bachelor's degree for students who started at a community college and transferred to a 4-year institution. Earning the associate's degree may not promote bachelor's degree attainment if the credits earned at the community college do not transfer, and research has shown that credit loss is both common and negatively associated with baccalaureate attainment (Giani, 2019;Monaghan & Attewell, 2015;Simone, 2014; U.S. Government Accountability Office, 2017). Associate's degree type may also influence bachelor's degree completion, as Kopko and Crosta (2016) found that transfer-oriented associate degrees have a significant positive impact on completing a bachelor's degree within 6 years while workforce-oriented degrees do not have an impact on baccalaureate completion.…”
Section: Reverse Credit Transfer and University Outcomesmentioning
confidence: 99%
“…However, Turk (2018) found that earning an associate's degree prior to transfer has no impact on the likelihood of completing a bachelor's degree for students who started at a community college and transferred to a 4-year institution. Earning the associate's degree may not promote bachelor's degree attainment if the credits earned at the community college do not transfer, and research has shown that credit loss is both common and negatively associated with baccalaureate attainment (Giani, 2019;Monaghan & Attewell, 2015;Simone, 2014; U.S. Government Accountability Office, 2017). Associate's degree type may also influence bachelor's degree completion, as Kopko and Crosta (2016) found that transfer-oriented associate degrees have a significant positive impact on completing a bachelor's degree within 6 years while workforce-oriented degrees do not have an impact on baccalaureate completion.…”
Section: Reverse Credit Transfer and University Outcomesmentioning
confidence: 99%
“…Community college transfer pathways are increasingly formalized through articulation agreements at the state, system, and institutional levels (Hodara et al, 2017). However, the efficacy of these policies in increasing transfer is inconclusive and varies across states and institutions (Anderson et al, 2006;Eaton, 1994;Giani, 2019;Kopko & Crosta, 2016;Roksa, 2006Roksa, , 2009. The effectiveness of articulation agreements in STEM contexts is particularly constrained by rigidity in how credits transfer between institutions, highly sequenced coursework, disagreement among faculty members about the content of foundational STEM courses, and perceptual concerns over "rigor" of prerequisite coursework, particularly in math courses.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the CAA revisions appeared to have a negative effect on excesscredit-earning behavior among White students, a positive result; however, the policy revisions were also related to an increase in excess credit earning among Black students 3,4 . Fink et al (2018) found nationally that Black students experienced more excess credit accumulation, while Giani (2019) found that students of Color were more likely to experience credit loss. Giani further posits that underserved students may need additional support as they navigate the transfer process, and their higher likelihood of credit loss is a symptom of unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…Fink and colleagues (2018) discovered that Black students often attempt greater numbers of excess credits in their educational journeys than do their White counterparts. Furthermore, Giani (2019) found that while all transfer students in North Carolina lose an average of 7.2% of their earned community college credits when they matriculate to a state university, "students of Color were significantly more likely to experience credit loss compared to White students" (p. 24). Each of these studies reveal the disparate outcomes that are likely to be experienced by students of Color.…”
Section: Students Of Color and Community College Transfermentioning
confidence: 99%
See 1 more Smart Citation